Job turnover, risk sharing, and regional wages in Western Germany - Daniel F. Heuermann (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2008)
We test Krugman's (1991) notion of risk sharing in pooled labor markets as one of the micro-foundations of agglomeration economies, i.e. we examine whether firms share risks from idiosyncratic and sector specific shocks through labor pooling. Estimating wage functions we find that job turnover depresses wages at the regional and the firm level, indicating that firms incur significant adjustment costs when experiencing productivity shocks. On the regional level, industrial specialization and diversification mitigate wage depressing effects of different types of employment shocks. On the firm level, shock intensive firms are found to be more productive when being located in spatial proximity to firms with large but opposite employment shocks. Both findings provide evidence that labor pooling matters as a source of agglomeration economies by allowing firms to share employment risks. However, we find only weak evidence for shock intensive industries to be more concentrated, suggesting that agglomeration costs exceed the benefits from risk sharing.
Keywords: R12; R30; J31; J63; 330; Marshallian Externalities; Labor Pooling; Specialization; Idiosyncratic Shocks